Comparative Analysis of Semiconductor Power Losses of Galvanically Isolated Quasi-Z-Source and Full-Bridge Boost DC-DC Converters - Kosenko, Roman; Liivik, Liisa; Chub, Andrii; Velihorskyi, Oleksandr (Electrical, Control and Communication Engineering, 2015)
This paper compares semiconductor losses of the galvanically isolated quasi-Z-source converter and full-bridge boost DC-DC converter with active clamping circuit. Operation principle of both converters is described. Short design guidelines are provided as well. Results of steady state analysis are used to calculate semiconductor power losses for both converters. Analytical expressions are derived for all types of semiconductor power losses present in these converters. The theoretical results were verified by means of numerical simulation performed in the PSIM simulation software. Its add-on module “Thermal module” was used to estimate semiconductor power losses using the datasheet parameters of the selected semiconductor devices. Results of calculations and simulation study were obtained for four operating points with different input voltage and constant input current to compare performance of the converters in renewable applications, like photovoltaic, where input voltage and power can vary significantly. Power loss breakdown is detailed and its dependence on the converter output power is analyzed. Recommendations are given for the use of the converter topologies in applications with low input voltage and relatively high input current.